Oxygen-driven 2-furfural accumulation and its influence on beer sensory stability - Mukoid, Roman; Bulii, Yurii; Kiriienko, Serhii (My University, 2025)
Досліджено, що концентрація 2-фурфуралю та інтенсивність його утворення залежить від часу контакту солоду, сусла і пива з киснем повітря. Зростання його концентрації призводить до погіршення смакових властивостей пива та прискореного його старіння. Для запобігання утворення продуктів окиснення та підтримання концентрації 2-фурфуралю в межах 4-10 мкг/дм3 період зберігання подрібненого солоду не повинний перевищувати 50 хв. Найбільше 2-фурфуралю утворюється при високих температурах під час кип`ятіння сусла з хмелем: протягом 90 хв його концентрація зростає в шість разів (від 122 до 793 мкг/дм3). Підвищення концентрації кисню від 20 до 120 мкг/дм3 під час бродіння сусла і фільтрування молодого пива призводить до збільшення концентрації 2-фурфуралю в ньому від 56,6 до 185,2 мкг/дм3. При мінімальному ступеню пастеризації його концентрація в пиві зростає майже вдвічі (від 56 до 104 мкг/дм3). При концентрації 2-фурфуралю в межах 150-200 мкг/дм3 пиво набуває окиснених нот і втрачає свою свіжість. У разі присутності в газовому просторі пляшки кисню вміст цієї сполуки в пиві зростає на 262 % (від 107 до 388 мкг/дм3), що погіршує якість пива. Для вимірювання вмісту продуктів окиснення і концентрації 2-фурфуралю в сировині і готовому продукті доцільно використовувати метод ультрафіолетової спектрофотометрії. Отримані цим методом результати корелюються із даними, отриманими хроматографічним методом. The concentration of 2-furfural and the intensity of its formation depend directly on the duration and degree of oxygen exposure during all stages of malt handling, wort production, and beer processing. As oxygen initiates a cascade of oxidative and thermal degradation reactions, the level of 2-furfural progressively increases, leading to deteriorated flavor, premature aging, and the development of stale, cardboard-like notes in the final product. To prevent excessive oxidation and maintain 2-furfural levels within the desirable range of 4–10 μg/l, the storage time of milled malt should not exceed 50 minutes, as prolonged exposure to air promotes early oxidative reactions already at the raw material stage. The most intensive formation of 2-furfural occurs during wort boiling with hops at elevated temperatures, where thermal degradation processes accelerate dramatically: within a 90-minute boil, its concentration increases six fold, rising from 122 to 793 μg/l. Oxygen uptake during subsequent stages also plays a crucial role. When dissolved oxygen increases from 20 to 120 μg/l during wort fermentation and green beer filtration, the concentration of 2-furfural rises accordingly – from 56.6 to 185.2 μg/l. Heat treatment further contributes to this process: even minimal pasteurization nearly doubles the level of 2-furfural (from 56 to 104 μg/l). Once its concentration reaches 150–200 μg/l, beer begins to exhibit clear oxidized notes, loses freshness, and shows noticeable sensory deterioration. Moreover, the presence of oxygen in the bottle headspace drastically accelerates this process, increasing 2-furfural content by 262% (from 107 to 388 μg/l), which severely compromises beer quality and shortens its shelf life. Ultraviolet spectrophotometry is recommended for measuring oxidation products and 2-furfural in raw materials and finished beer, as its results correlate well with chromatographic data.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; malt; beer wort; boiling; fermentation; hops; essential oils; ефірні олії; пиво; солод; сусло пивне; кип’ятіння сусла; хміль